2018
DOI: 10.1016/j.ihj.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Baseline C-reactive protein levels and prognosis in patients with infective endocarditis: A prospective cohort study

Abstract: BackgroundEarly diagnosis and risk-stratification among infective endocarditis (IE) patients are limited by poor microbiological yield and inadequate characterization of vegetations. A simple tool that can predict adverse outcomes in the early phase of management is required.AimTo study the prognostic value of C-reactive protein (CRP) levels at admission and its role in predicting various clinical outcomes.MethodsIn a prospective study of consecutive IE patients diagnosed by modified Duke’s criteria, we measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
2
22
0
1
Order By: Relevance
“…Among laboratory investigations, we found a high level of CRP within three days from hospital admission confirming that high levels of CRP levels may be an inexpensive laboratory test to take to account for decision-making in febrile patients to prompt them in performing a TTE as also suggested by other studies [30]. This study analyzing the demographic variables found that age and gender influenced IE surgery therapy.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Among laboratory investigations, we found a high level of CRP within three days from hospital admission confirming that high levels of CRP levels may be an inexpensive laboratory test to take to account for decision-making in febrile patients to prompt them in performing a TTE as also suggested by other studies [30]. This study analyzing the demographic variables found that age and gender influenced IE surgery therapy.…”
Section: Discussionsupporting
confidence: 83%
“…This result may be explained considering that males with IE have been reported to have a high probability of cardiac surgery as compared with females. Recent studies confirm that male gender and old age are variables that determine who may need surgery irrespective of the clinical status and comorbidities [30].…”
Section: Discussionmentioning
confidence: 99%
“…Definition of Cut-Off Points of CRP, on Week 3 and 4 That Could Predict Death of A Patient During the Remaining Follow-Up.dictive of mortality, major complications, embolic events, and need for urgent surgery, and also a CRP >40 mg/l predicted adverse outcomes with a sensitivity of 73% and specificity of 99%(9). Similar to our results, in the study ofHeiro et al…”
supporting
confidence: 90%
“…Serum C‐reactive protein (CRP), which is produced by the liver, is an important inflammatory biomarker. An elevated CRP level (CRP > 40 mg/L) is an independent predictor of EE 24 . CRP activates the coagulation cascade by inducing the production of TF that modify the platelet function within the vegetation causing it to become more friable.…”
Section: Predictors For Eementioning
confidence: 99%